Characterization of the immune response and evaluation of the protective capacity of rSsnA against Streptococcus suis infection in pigs. (August 2016) - Gómez-Gascón, Lidia; Cardoso-Toset, Fernando; Tarradas, Carmen; Gómez-Laguna, Jaime; Maldonado, Alfonso; Nielsen, Jens; Olaya-Abril, Alfonso; Rodríguez-Ortega, Manuel J.; Luque, Inmaculada
Highlights: An experimental challenge against Streptococcus suis serotype 2 in a pig model was used to validate the efficacy of the cell-wall protein SsnA as vaccine candidate combined with ALOH plus Quil A as adjuvants (Wellvac-suis). Immunization of piglets with Wellvac-suis elicits a significant humoral antibody response against Strepococcus suis . However, the antibody response is not reflected in protection in our conventional vaccination model. The combination of ALOH (250 mg/ml) and Quil A (260 μg/ml) with rSsnA protein induce predominantly Th2-like responses. Abstract: The efforts made to develop vaccines against Streptococcus suis have failed because of lack of common antigens cross-reactive against different serotypes of this species. The cell wall-anchored proteins can be good vaccine candidates due to their high expression and accessibility to antibodies, among these, a cell-wall protein, DNA-nuclease (SsnA), present in most of the S. suis serotypes and clinical isolates collected from infected pigs, was selected. An experimental challenge against S. suis serotype 2 in a pig model was used to validate the efficacy of recombinant SsnA combined with aluminium hydroxide plus Quil A as adjuvants, previously tested in mice by our research group with good results. In our study, clinical characteristics, bacterial load and spread, haematological and immunological parameters and the antibody response, including the opsonophagocytosis analysis of the sera were evaluated. Moreover the composition of peripheral blood leukocyte populations was studied in infected animals. The results show that the immunization of piglets with rSsnA elicits a significant humoral antibody response. However, the antibody response is not reflected in protection of pigs that are challenged with a virulent strain in our conventional vaccination model. Further studies are necessary to evaluate the use of rSsnA as a vaccine candidate for swine.